Evaluation of Molecular Epidemiology, Clinical Characteristics, Antifungal Susceptibility Profiles, and Molecular Mechanisms of Antifungal Resistance of Iranian Candida parapsilosis Species Complex Blood Isolates - Arastehfar, Amir; Daneshnia, Farnaz; Najafzadeh, Mohammad Javad; Hagen, Ferry; Mahmoudi, Shahram; Salehi, Mohammadreza; Zarrinfar, Hossein; Namvar, Zahra; Zareshahrabadi, Zahra; Khodavaisy, Sadegh; Zomorodian, Kamiar; Pan, Weihua; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Clonal expansion of fluconazole resistant (FLZ-R) Candida parapsilosis isolates is increasingly being identified in many countries, while there is no study exploring the antifungal susceptibility pattern, genetic diversity, and clinical information for Iranian C. parapsilosis blood isolates. Candida parapsilosis species complex blood isolates (n=98) were recovered from nine hospitals located in three major cities, identified by MALDI-TOF MS, and their genetic relatedness was examined by AFLP fingerprinting. Antifungal susceptibility testing followed CLSI-M27-A3 and ERG11, MRR1 and hotspots 1/2 (HS1/2) of FKS1 were sequenced to assess the azole and echinocandin resistance mechanisms, respectively. Ninety-four C. parapsilosis and four Candida orthopsilosis isolates were identified from 90 patients. Only 43 patients received systemic antifungal drugs with fluconazole as the main antifungal used. The overall mortality rate was 46.6% (42/90) and death mostly occurred for those receiving systemic antifungals (25/43) relative to those not treated (17/47). Although, antifungal-resistance was rare, one isolate was multidrug-resistant (FLZ=16µg/ml and micafungin=8µg/ml) and the infected patient showed therapeutic failure to FLZ prophylaxis. Mutations causing azole and echinocandin resistance were not found in the genes studied. AFLP revealed five genotypes (G) and G1 was the main one (59/94; 62.7%). Clinical outcome was significantly associated with city (P=0.02, α<0.05) and Mashhad was significantly associated with mortality (P=0.03, α<0.05). Overall, we found a low level of antifungal resistance for Iranian C. parapsilosis blood isolates, but the noted MDR strain can potentially become the source of future infections and challenge the antifungal therapy in antifungal-naïve patients. AFLP typing results warrants confirmation using other resolutive typing methods.